Agile Methodology for Design and Implementation of Databases and Websites for Sales and Administration of Computer Hardware. - Duong-Trung, Nghia (Cuvillier Verlag, 2017)
In the theory world, engineering characteristic is one of the most influentially significant elements in Software Development and it requires an enduring research in other to apprehend and apply. Comprehensively understanding the Engineering characteristic is very hard and smoothly implementing is thousand times harder. The aim of this project "Design and Implementation of a Database and a Website for Sales and Administration of Computer Hardware" as well as this master thesis is the effort of bringing the Engineering characteristic which has perfectly been described in books, lectures and assignments into a real project in business. At this point, the differences come out and demand a new thinking concept: thinking as a developer and thinking as a programmer. There is no final version in software development since new business requirements appear rapidly. As the result, particular software needs repairing, updating, maintaining and enhancing time after time. And how can we do all these things without understanding the software we are going to manipulate? This project and master thesis will look at the Engineering characteristic as an eye of description and documentation in the assumption that everyone else can read this thesis and continuously maintain and develop the project easily.